What are art and artistic value? Some contributions based on Jon Elster’s theory of creativity in the arts - Tena Sánchez, Jordi; Centellas, Indira (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This paper, building on Jon Elster’s theory of creativity in the arts, tries to offer a draft of a definition of art as well as the basis for a theory of artistic value. It is argued that a work of art is a human creation made with the intention of inducing an aesthetic experience, as well as that the main value of a work of art consists on its capacity to produce aesthetic and non-aesthetic emotions. This conception implies some serious difficulties for some important forms of contemporary art, as conceptual art.
Keywords: art theory; contemporary art; Postmodernism; Aesthetic emotions; Aesthetic value